2021
DOI: 10.1073/pnas.2100970118
|View full text |Cite
|
Sign up to set email alerts
|

Pairing facts with imagined consequences improves pandemic-related risk perception

Abstract: The COVID-19 pandemic reached staggering new peaks during a global resurgence more than a year after the crisis began. Although public health guidelines initially helped to slow the spread of disease, widespread pandemic fatigue and prolonged harm to financial stability and mental well-being contributed to this resurgence. In the late stage of the pandemic, it became clear that new interventions were needed to support long-term behavior change. Here, we examined subjective perceived risk about COVID-19 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 87 publications
(134 reference statements)
5
37
1
Order By: Relevance
“…In other words, we were asking for these judgments during the absolute peak of the crisis and when our participants faced the greatest risk of infection. It is difficult to determine the actual risk participants faced as we only collected information on the relatively coarse level of the state they lived in, and in any case, recent work has found that lay estimations of risk during the pandemic are somewhat more optimistic than objective calculations of risk (Sinclair, Hakimi, Stanley, Adcock, & Samanez-Larkin, 2021). As a result, it is unclear what kind of influence this timing had on our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, we were asking for these judgments during the absolute peak of the crisis and when our participants faced the greatest risk of infection. It is difficult to determine the actual risk participants faced as we only collected information on the relatively coarse level of the state they lived in, and in any case, recent work has found that lay estimations of risk during the pandemic are somewhat more optimistic than objective calculations of risk (Sinclair, Hakimi, Stanley, Adcock, & Samanez-Larkin, 2021). As a result, it is unclear what kind of influence this timing had on our results.…”
Section: Discussionmentioning
confidence: 99%
“…That said, there are also hints about how policy communication could be improved, both from our results and from other recent investigations. Recent work has suggested that making people consider bad outcomes (which we argue they do not consider otherwise) may make them more likely to comply with public health measures (Sinclair, Hakimi, Stanley, Adcock, & Samanez-Larkin, 2021). Our findings also suggest other potential measures that might reduce judgments of overreaction and potentially compliance, such as emphasizing the specific causal mechanisms by which the intervention will prevent or mitigate bad outcomes (Study 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For others, risk aversion driven by pandemic-related concerns increased, leading to lowered involvement in risky and greater involvement in health-promoting behaviors (e.g., increased hand hygiene; Shilo and Mor, 2020 ; Starks et al, 2020 ; Khan et al, 2021 ; Magnan et al, 2021 ; Shachat et al, 2021 ). Perceived risk of COVID-19 was associated with greater involvement in health-promoting behaviors that supported COVID-19 prevention (e.g., hand hygiene, maintaining social distance; Wise et al, 2020 ; Qin et al, 2021 ; Rui et al, 2021 ; Sinclair et al, 2021 ). Non-pandemic related health-promoting behaviors, such as blood donation and vaccination, were encouraged throughout the COVID-19 pandemic because, despite an element of risk, the benefits of these health-promoting behaviors outweighed potential costs.…”
Section: Introductionmentioning
confidence: 99%
“…It is not enough to rely on predictive modeling of COVID-19 spread and vaccine uptake to guide behavioral change 3 ; identifying actual behavioral markers of vaccine hesitancy and unwillingness is the crucial next step to reduce the severity and spread of COVID-19 5 , particularly given continued emergence of COVID-19 variants. Greater insight into the decision-making processes involved in vaccination choices can lead to strategies to better align behavior with medical and public health recommendations 6 .…”
Section: Introductionmentioning
confidence: 99%